Isaac Taylor Tichenor : the creation of the Baptist new South - Williams, Michael E. (Michael Edward), 1960- (Tuscaloosa : University of Alabama Press, 2018)
"Michael E. Williams examines Tichenor's entire life and work. He documents the methodologies Tichenor used to rally Southern Baptist support around its struggling Home Mission Board, which defined the makeup of the Southern Baptist Convention and defended the territory of the Convention. Williams contends that Tichenor's role in shaping Southern Baptists as they became the largest denomination in the South was crucial in determining both the identities of the region and the SBC."--Jacket.
1. The emerging denominationalist : Tichenor as pastor and Southern Baptist leader, 1825-60 -- 2. The emerging sectionalist : Tichenor as confederate chaplain and pastor, 1861-65 -- 3. Building the new South : Tichenor as pastor and mining executive, 1865-72 -- 4. Educating the new South : Tichenor as college president, 1872-82 -- 5. A new mission agency for a new South : reinventing the Southern Baptist Home Mission Board -- 6. Expanding the vision : from the tropics to the mountains -- 7. "Our Southland" : Tichenor defines Southern Baptist territory -- 8. Buildings, books, and battles : Tichenor defends Southern Baptist territory.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (EBSCO, viewed May 10, 2018).
Added to collection customer.56279.3 - Master record variable field(s) change: 050, 082
Keywords: Tichenor, I. T. -- 1825-1902.; Southern Baptist Convention -- History -- 19th century; Tichenor, I. T. -- 1825-1902.; Southern Baptist Convention; Southern Baptist Convention; Verenigde Staten; RELIGION / Christianity / Baptist; History; Electronic books